Paula Gomes-Ribeiro, Júlia Durand, Joana Freitas & Filipe Gaspar (eds.), Música, género, sexualidades: Musical Trouble... After Butler (Famalicão, Húmus, 2021) - Braga, Helena Lopes (Revista Portuguesa de Musicologia, 2023)
Recensão: Paula Gomes-Ribeiro, Júlia Durand, Joana Freitas & Filipe Gaspar (eds.), Música, género, sexualidades: Musical Trouble... After Butler (Famalicão, Húmus, 2021)